What the ASEAN Economic Community Will Mean for Businesses - United Nations Economic; Social Commission for Asia; the Pacific; David Abonyi; Masato Abe (United Nations, 2016)
With the ASEAN Economic Community (AEC) coming into effect, the main purpose of this publication is to serve as a resource to businesses, particularly in Myanmar and the other CLMV countries, in navigating the coming changes. The central conclusion of this guidebook is that despite the numerous opportunities the AEC will provide to the private sector, the reality for most CLMV businesses is that they will need to focus, at least initially, primarily on remaining competitive domestically in a more open and regionally integrated environment. This is due to several disadvantages they face in comparison to companies from the more economically powerful countries in the region. This includes underdeveloped domestic and cross-border infrastructure, less competitive human resources, lower quality technology and equipment, and a more challenging business environment.